2022
DOI: 10.1057/s41270-022-00164-9
|View full text |Cite
|
Sign up to set email alerts
|

Do E-wallets trigger impulse purchases? An analysis of Malaysian Gen-Y and Gen-Z consumers

Abstract: This study investigates the factors influencing Generation Y and Z’s satisfaction and perceived enjoyment of using E-wallet. This paper further assesses whether consumers perceived enjoyment and satisfaction with using E-wallet would significantly affect their impulsive buying behavior. PLS-SEM was conducted based on 201 valid responses from active E-wallet users collected through an online survey. The results revealed that perceived interactivity and subjective norm positively influenced perceived enjoyment a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
47
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 104 publications
8
47
0
3
Order By: Relevance
“…According to research, 41% of Generation Z customers are impulsive shoppers, followed by 34% of Millennials and 32% of Generation X ( Djafarova and Bowes, 2021 ). Gen Z consumers are more persuasive while making purchases ( Lee et al, 2022 ). They want new products faster ( Agrawal, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…According to research, 41% of Generation Z customers are impulsive shoppers, followed by 34% of Millennials and 32% of Generation X ( Djafarova and Bowes, 2021 ). Gen Z consumers are more persuasive while making purchases ( Lee et al, 2022 ). They want new products faster ( Agrawal, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is more necessary to explore factors influencing impulsive buying behavior from the perspective of consumers' intrinsic characteristics in electronic commerce. In recent years, more and more scholars have begun investigating this issue (e.g., [34][35][36]). While some studies found that demographic characteristics can influence impulsive buying behavior (e.g., [37][38][39]), others observed that personality also has a significant influence on impulsive buying behavior, most often based on the big-five model (e.g., [40][41][42][43][44]).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the consumers are divided into innovators, early adopters, early majority, middle majority, late majority, and laggards, so according to their purchasing power and lifestyle (Gutter et al, 2010;Kutaula et al, 2022;Schiessl et al, 2022).The brands should modify their products and marketing strategies to provide enough information and satisfaction to become differentiate brand in the market that is ultimately the target of the consumer to purchase when they get involved in their life and social circle (Di Crosta et al, 2021;Goraya et al, 2020;Taghikhah et al, 2021;Xiao et al, 2011). Additionally, brands are working on the strategy of providing emotional importance to the consumers because the consumer who are emotionally attached to the brands, just got satisfaction from the same brand (Hoe & Mansori, 2018;Lee et al, 2022;Shankar, 2021).As result, they become potential and loyal consumers of that particular brand in the large or target market (Eichinger et al, 2022;Emekci, 2019;Khraim, 2011;Ottosson & Kindström, 2016). As the results of hypothesis 5 demonstrate there is a significant relationship between value perception and consumer satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Consumer lifestyle refers to the attitude and values including the perception of consumers that they have for any brand in the large market (Ahn & Kwon, 2022).At the same time, their value is not only cognitive but is action-oriented because it is noted that purchasing is directly related to the values of the people (Hu & Tracogna, 2021). Value perception has also a significant influence on consumer satisfaction, because if the brands are providing products or services according to the set of values of a consumer's need or want, then as result, the consumers would be satisfied and they would develop a long-term relationship with that brand (Lee et al, 2022;Thompson et al, 2014). Hypothesis 3.…”
Section: Marketing Innovation Consumer Lifestyle Value Perception And...mentioning
confidence: 99%
See 1 more Smart Citation